Sistem Informasi Akuntansi Persediaan Bahan Baku Socket Helm Berbasis Vb.Net Pada PT Global Indotech Industry - Arif Maulana Yusuf; Apit Priatna; Indaryono Indaryono; Dewi Widyana (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
The implementation of activities in PT Global Indotech Industry has run quite well but has not used a computer-based system to check and calculate raw materials. As the author observed, it turns out there are still problems that occur in checking and calculating the raw material supplies of helmet sockets, such as miscalculating raw material stocks and slow checking of stock availability of raw materials, so that it will disrupt scheduled production systems and can harm the company. Based on the things mentioned above, the author argues that in order to overcome the problem in question, it is necessary to design and implement a system that is integrated between related functions in a system using Microsoft Visual Studio 2008 and its database Microsoft SQL Server 2005 while system design includes design input output, DFD, ERD, data and database dictionary. With the implementation of this system, it is expected that the process of checking and calculating helmet socket raw material supplies for the future can run smoothly and on time.